2016
DOI: 10.1038/srep31975
|View full text |Cite
|
Sign up to set email alerts
|

Higher FT4 or TSH below the normal range are associated with increased risk of dementia: a meta-analysis of 11 studies

Abstract: Observational studies of thyroid function and dementia have reported conflicting results. We reviewed cohort and case-control studies from MEDLINE, EMBASE, Web of Science and the Cochrane Library that focused on the association between serum thyroxine, thyrotropin and dementia. A total of 24,952 participants from three case-control and eight cohort studies were included. The relationships between dementia and the per standard deviation (SD) increment of free thyroxine (FT4) (random relative ratio (RR) = 1.08, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 58 publications
4
32
1
Order By: Relevance
“…Lack of TH in utero and in early life causes severe cognitive impairment, with extensive white matter pathology (Rosman, 1972). In later life, hyperthyroidism has been often associated with cognitive decline (Akintola et al, 2015;Chaker et al, 2018;Chaker et al, 2016;Moon, 2016;Moon et al, 2014;Rieben et al, 2016;Tan and Vasan, 2009;Wu et al, 2016;Yeap et al,2012). A recent PubMed search using "(thyroid or thyroxine) and (Alzheimer's or dementia)" returns >600 published papers.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of TH in utero and in early life causes severe cognitive impairment, with extensive white matter pathology (Rosman, 1972). In later life, hyperthyroidism has been often associated with cognitive decline (Akintola et al, 2015;Chaker et al, 2018;Chaker et al, 2016;Moon, 2016;Moon et al, 2014;Rieben et al, 2016;Tan and Vasan, 2009;Wu et al, 2016;Yeap et al,2012). A recent PubMed search using "(thyroid or thyroxine) and (Alzheimer's or dementia)" returns >600 published papers.…”
Section: Discussionmentioning
confidence: 99%
“…A routine screening test, free T3, free T4, and TSH were assessed in the cases and 105 control subjects with mean age - 62 years, which revealed subclinical hyperthyroidism and AD to have a consistent association [ 24 ]. A meta-analysis of 11 studies by Yue Wu et al with a total of 24,952 participants, established relationships between dementia and the per SD increment of free thyroxine (FT4) (RR = 1.08, 95% CI 1.00-1.17) and thyroid-stimulating hormone (TSH) (fixed RR = 0.91, 95% CI 0.84-0.99) [ 25 ]. An increased risk of dementia (fixed RR = 1.60, 95% CI 1.27-2.00) was found with TSH levels below the normal range and with higher FT4 levels.…”
Section: Reviewmentioning
confidence: 99%
“…An increased risk of dementia (fixed RR = 1.60, 95% CI 1.27-2.00) was found with TSH levels below the normal range and with higher FT4 levels. But low or high categories of TSH in men did not show any association with the risk of dementia [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…In the present study, we grouped all dementia diagnoses together to be able to have enough statistical power for the analyses. However, this is also performed in other studies as well [4, 8, 10], and in the clinical situation this is more relevant for doctors as well as patients. As dementia is a cluster of disorders developing over many years, patients may die as a result of other causes before getting a dementia diagnosis, i.e., because of a competing risk, which could affect the results.…”
Section: Conclusion and Limitationsmentioning
confidence: 94%
“…A recent study found hypothyroidism to be associated with cerebrovascular diseases but not with AD pathology [6]. Higher levels of free thyroxin have repeatedly been shown to be associated with incident dementia [7, 8]. Animal models have shown hypothyroidism to induce the amyloidogenic pathway of amyloid precursor protein processing in the hippocampus [9].…”
Section: Introductionmentioning
confidence: 99%